Implementation of Multicultural Islamic Religious Education at Madrasah Aliyah Negeri Seluma, Bengkulu - Nur Hidayat (PT. Islamic Research Publisher, 2023)
This study discusses the implementation of multicultural Islamic religious education in PAI learning at MAN Seluma Bengkulu Province . Multicultural as a perspective can be a solution to mutual acceptance of differences, open to each other and maintain inter-religious harmony. This research aims to reveal How implementation multicultural values at MAN Seluma Bengkulu Province . In this study, the type of research used is descriptive qualitative research. Processed data obtained through observation techniques, interviews and documentation. Based on the results of the research, it shows that the implementation of multicultural values at MAN Seluma, Bengkulu Province is carried out in various stages, both the planning stage, the implementation stage and the evaluation stage